A student is trying to solve the system of two equations given below:

Equation P: y + z = 6
Equation Q: 5y + 9z = 1

Which of the following is a possible step used in eliminating the y-term?

(y + z = 6) ⋅ 9
(y + z = 6) ⋅ −5
(5y + 9z = 1) ⋅ 9
(5y + 9z = 1) ⋅ 5

Respuesta :

tonb
I would say B. By multiplying the first equation by -5, you create -5y. If you add that to the second equation, your cancelling out the 5y term, and get a new equation with only z and a constant.

Answer:

the answer is B